Plasma microbial cell-free DNA characterization in different populations based on the droplet digital PCR method: a multi-cohort study - Du, Juan; Zhang, Dong; Wang, Fengliu; Shang, Xuesong; Zhang, Jingjia; Wang, Guanhua; Ding, Jingwen; Ren, Aiwu; Jing, Shuang; Bai, Lu; Liu, Ying; Zhao, Ye; et al. (Frontiers in Microbiology, 2025)
BackgroundPlasma microbial cell-free DNA (mcfDNA) is a key biomarker for diagnosing bloodstream infections (BSIs), which contribute significantly to morbidity and mortality, particularly in patients with severe trauma, chronic illnesses, or immunosuppressive conditions. However, the baseline distribution of mcfDNA in different populations remains unclear. This study characterizes plasma mcfDNA profiles across various human populations.MethodsA total of 300 blood samples were collected from 10 groups: healthy individuals (Group A), patients with chronic diseases but no infections (Group B1–B7), patients with mild-to-moderate infections (Group C), and patients meeting sepsis criteria (Group D). Multiplex droplet digital PCR (ddPCR) was used to detect mcfDNA from 10 common sepsis-causing bacterial species, two fungal species, and three herpesviruses (HSV-1, Epstein–Barr virus [EBV], and Cytomegalovirus [CMV]).ResultsMost pathogens in all groups showed low mcfDNA copy concentrations (~100 copies/mL), forming a baseline. Group A had no pathogens exceeding this level, while Group B showed elevated E. coli and S. maltophilia (102–104 copies/mL). In Group C, 53 pathogens were detected above baseline, with EBV, CMV, and HSV-1 as the most common (copy concentrations 102–104 copies/mL). In Group D, 57 pathogens exceeded baseline, primarily EBV, K. pneumoniae, A. baumannii, E. faecium, and CMV. Although statistical analysis showed no significant differences in pathogen distribution between Groups C and D, Gram-negative bacteria were more prevalent in Group D (70% vs. 53.3%, OR = 2.03), while viral pathogens were more frequently detected in Group C (93.3% vs. 76.7%, OR = 0.24). The microbial profiles and mcfDNA copy concentrations in Groups C and D were similar (102–104 copies/mL), distinguishing them from Groups A and B.ConclusionThis study provides a comprehensive characterization of mcfDNA across different health states, demonstrating the utility of ddPCR in detecting microbial infections. These findings contribute to refining infection diagnostics and improving early detection strategies for BSIs and sepsis.